Response of a marine-terminating Greenland outlet glacier to abrupt cooling 8200 and 9300 years ago - Young, ás E.; Briner, Jason P.; Axford, Yarrow; Csatho, Beata; Babonis, Greg S.; Rood, Dylan H.; Finkel, Robert C. (Geophysical Research Letters, 2011)
Long-term records of Greenland outlet-glacier change extending beyond the satellite era can inform future predictions of Greenland Ice Sheet behavior. Of particular relevance is elucidating the Greenland Ice Sheet's response to decadal- and centennial-scale climate change. Here, we reconstruct the early Holocene history of Jakobshavn Isbræ, Greenland's largest outlet glacier, using 10Be surface exposure ages and 14C-dated lake sediments. Our chronology of ice-margin change demonstrates that Jakobshavn Isbræ advanced to deposit moraines in response to abrupt cooling recorded in central Greenland ice cores ca. 8,200 and 9,300 years ago. While the rapid, dynamically aided retreat of many Greenland outlet glaciers in response to warming is well documented, these results indicate that marine-terminating outlet glaciers are also able to respond quickly to cooling. We suggest that short lag times of high ice flux margins enable a greater magnitude response of marine-terminating outlets to abrupt climate change compared to their land-terminating counterparts.

Regional beryllium-10 production rate calibration for late-glacial northeastern North America - Balco, Greg; Briner, Jason; Finkel, Robert C.; Rayburn, John A.; Ridge, John C.; Schaefer, Joerg M. (Quaternary Geochronology, 2009)
The major uncertainty in relating cosmogenic-nuclide exposure ages to ages measured by other dating methods comes from extrapolating nuclide production rates measured at globally scattered calibration sites to the sites of unknown age that are to be dated. This uncertainty can be reduced by locating production rate calibration sites that are similar in location and age to the sites to be dated. We use this strategy to reconcile exposure age and radiocarbon deglaciation chronologies for northeastern North America by compiling (10)Be production rate calibration measurements from independently dated late-glacial and early Holocene ice-marginal landforms in this region. 10Be production rates measured at these sites are 6-12% lower than predicted by the commonly accepted global 10Be calibration data set used with any published production rate scaling scheme. In addition, the regional calibration data set shows significantly less internal scatter than the global calibration data set. Thus, this calibration data set can be used to improve both the precision and accuracy of exposure dating of regional late-glacial events. For example, if the global calibration data set is used to calculate exposure ages, the exposure-age deglaciation chronology for central New England is inconsistent with the deglaciation chronology inferred from radiocarbon dating and varve stratigraphy. We show that using the regional data set instead makes the exposure age and radiocarbon chronologies consistent. This increases confidence in correlating exposure ages of ice-marginal landforms in northeastern North America with glacial and climate events dated by other means. (c) 2008 Elsevier Ltd. All rights reserved.
id: 2034; PT: J; UT: WOS:000265163500003